The sustainability revolution : portrait of a paradigm shift. - Edwards, Andres R., ....- (Gabriola Island : New Society, 2005)
Sustainability has become a buzzword in the last decade, but its full meaning is complex, emerging from a range of different sectors. In practice, it has become the springboard for millions of individuals throughout the world who are forging the fastest and most profound social transformation of our time - the Sustainability Revolution. The Sustainability Revolution paints a picture of this largely unrecognized phenomenon from the point of view of five major sectors of society: Community (government and international institutions) Commerce (business) Natural Resources (forestry, farming, fisheries, etc.) Ecological Design (architecture, technology) Biosphere (conservation, biodiversity, etc.). The book analyses sustainability as defined by each of these sectors in terms of the principles, declarations and intentions that have emerged from conferences and publications, and which serve as guidelines for policy decisions and future activities. Common themes are then explored, including: an
Emphasis on stewardship the need for economic restructuring promoting no waste and equitable distribution an understanding and respect for the principles of nature the restoration of life forms, and an intergenerational perspective on solutions. Concluding that these themes in turn represent a new set of values that define this paradigm shift, The Sustainability Revolution describes innovative sustainable projects and policies in Colombia, Brazil, India and the Netherlands and examines future trends. Complete with a useful resources list, this is the first book of its kind and will appeal to business and government policy makers, academics, and all interested in sustainability. Introduction : portrait of the sustainability revolution Ch. 1 The birth of sustainability Ch. 2 Sustainability and community Ch. 3 Sustainability and commerce Ch. 4 Sustainability and natural resources Ch. 5 Sustainability and ecological design Ch. 6 Sustainability and the biosphere Ch. 7 Future pathways
Keywords: Duurzaam lokaal beleid; Duurzame ontwikkeling; Ecologie; Milieu en economie